2007
DOI: 10.1074/jbc.m703464200
|View full text |Cite
|
Sign up to set email alerts
|

The ATPase Activity of the DNA Transporter TrwB Is Modulated by Protein TrwA

Abstract: Conjugative systems contain an essential integral membrane protein involved in DNA transport called the Type IV coupling protein (T4CP). The T4CP of conjugative plasmid R388 is TrwB, a DNA-dependent ATPase. Biochemical and structural data suggest that TrwB uses energy released from ATP hydrolysis to pump DNA through its central channel by a mechanism similar to that used by F 1 -ATPase or ring helicases. For DNA transport, TrwB couples the relaxosome (a DNA-protein complex) to the secretion channel. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…These proteins, by their capacity to direct this interaction, are crucial for the specificity of mobilization. It has been shown with the IncW plasmid R388 that membrane protein TrwB is responsible for coupling the relaxosome with the DNA transport apparatus (6,47). In general, the coupling proteins are specific (31).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins, by their capacity to direct this interaction, are crucial for the specificity of mobilization. It has been shown with the IncW plasmid R388 that membrane protein TrwB is responsible for coupling the relaxosome with the DNA transport apparatus (6,47). In general, the coupling proteins are specific (31).…”
Section: Discussionmentioning
confidence: 99%
“…NTDs are thought to mediate the coupling of T4CPs with cognate T4SS channels (14,(44)(45)(46)(47). We therefore engineered T4CPs consisting of the NTD from TraJ pKM101 joined to ⌬NTD variants of VirD4 At , VirD4 Ap , and VirD4 Ap (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The structural similarity between TrwB and well known molecular motors, such as F 1 -ATPase (8) or T7 gene 4 helicase (9), suggests that TrwB also operates as a motor, using energy released from ATP hydrolysis to pump DNA through its central channel (10). Recent biochemical data indicated that TrwB ATPase activity can be activated by DNA and/or by protein TrwA, a tetrameric protein that binds specifically at the origin of transfer of the plasmid (oriT) and facilitates TrwB assembly on DNA (11). The TrwA-TrwB system resembles other DNA-dependent molecular motors, such as the RuvA-RuvB recombination system, that target specific DNA structures for assembly as hexamers to pump DNA (12).…”
mentioning
confidence: 99%